0451 Association Of The Arousal Threshold With Inflammation And Sleepiness In Men With Obstructive Sleep Apnea. (27th April 2018) - Appleton, S; Eckert, D; Vakulin, A; Catcheside, P; McEvoy, D; Martin, S; Wittert, G; Adams, R J
Abstract: Introduction: Waking up too easily to minor airway narrowing (low respiratory arousal threshold: ArTH) is a key non-anatomical contributor to obstructive sleep apnea (OSA) pathophysiology. However, the extent to which a low ArTH phenotype contributes to daytime sleepiness and inflammation-related clinical sequelae in OSA is unclear. Accordingly, we determined relationships between ArTH, inflammation and sleepiness in a cohort of community dwelling men with OSA. Methods: The Men Androgen Inflammation Lifestyle Environment and Stress (MAILES) Study is a biomedical cohort of men aged ≥ 35y in Adelaide, South Australia. In 2008–10, men underwent biomedical assessment (including anthropometry, inflammatory markers) and in 2010–12, 837 men underwent home-based full unattended polysomnography (Embletta X100) and completed the Epworth Sleepiness Scale (ESS). ArTH was estimated using a 2014 published equation: -65.391 + 0.0636*age + 3.692*1 (male sex) - 0.0314*BMI - 0.108*apnea hypopnea index + 0.533*oxygen saturation nadir + 0.0906*hypopnea fraction. Low arousal threshold was also identified as two or more of: apnea hypopnea index<30; oxygen saturation nadir >82.5%; hypopnea fraction >58.3%. Inflammatory markers were log-transformed. Results: In 423 men with OSA (AHI≥10/hr), mean (SD) ArTH was -17.8cmH2 O (6.5). ArTh was significantly correlated with C-reactive protein (CRP, Pearson r= -0.118, p=0.018), and e-Selectin (e-SEL, r= -0.152, p=0.003) but not with myeloperoxidase (r= -0.01, p=0.84), tumor necrosis factor-alpha (r= -0.018, p=0.72), interleukin-6 (r= -0.096, p=0.057) or ESS scores (r= -0.091, p=0.065). In multiple regression models adjusted for age, BMI, and smoking, significant associations of ArTH with CRP (p=0.27) and eSEL (p=0.093) were confounded by age and obesity and did not persist. BMI and depression but not ArTH (unstandardized B coefficient p=0.28) explained ESS scores. The findings did not alter when ArTH was entered as a dichotomous variable (low vs high) into models. The null finding for sleepiness was also observed men with low-moderate OSA, i.e. AHI 10–30/hr (ArTH unstandardized B coefficient p=0.28). Conclusion: The ArTH is not independently associated with inflammation or excessive sleepiness in OSA. Support (If Any): The ResMed Foundation and NH&MRC of Australia.